Analysis of Shielded Metal Arc Welding (SMAW) with Current Variations Against Tensile Strength, Bending Strength, and Microstructure of API 5L X52 - Matin, Qowi; Haliq, Ridhwan; idhil ismail, andi; Jamil, Muchammad (Naval Architecture Department, Kalimantan Institut of Technology, 2024)
This study aims to analyze the effect of current variations on the V seam with a seam angle of 37.5° on the testing of mechanical properties and the appropriate welding method as a connector for two API 5L X52 materials using the Shielded Metal Arc Welding (SMAW) welding method. The current variation used is (70, 100, 115 A) in Sample A, the current variation is (70, 120, 130 A) in Sample B, and the current variation is (70, 125, 130 A) in Sample C. After the welding process is carried out, the samples are then tested for tensile, bending, observing macro structures, and microstructures. The test results obtained the highest value of tensile testing on current variations (70, 125, 130 A) with a value of 715.4 MPa, while the lowest value on current variations (70, 100, 115 A) with a value of 596.66 MPa. The results of the bending test show that the highest value is obtained in the current variation (70, 125, 130 A) with a value of 1417.93 MPa, while the lowest value is obtained in the current variation (70, 100, 115 A) with a value of 1289.01 MPa. The results of metallographic testing showed that the microstructure data on variations in the welding current strength of (70, 100, 115 A), (70, 120, 130 A), and (70, 125, 130 A) resulted in a phase that composed of ferrite and pearlite. The microstructure formed is influenced by the magnitude of the welding current used. The results of macro observations obtained porosity in the weld metal area.